Induksi mutasi Stevia rebaudiana dengan perendaman kolkisin secara in vitro (Induced mutation of Stevia rebaudiana through colchicine soaking in vitro) - Masna Maya SINTA; Ni Made Armini WIENDI; Syarifah Iis AISYAH (INDONESIAN RESEARCH INSTITUTE FOR BIOTECHNOLOGY AND BIOINDUSTRY, 2018)
Stevia rebaudiana Bert. is a plant producing steviol glycosides that have 200-300 times sweeter than sucrose. These steviol glycosides are produced in the leaves and then spread to all parts of the plant including stems. The use of superior stevia planting material is important for stevia sugar industry. One of the stevia breeding programme is to increase genetic diversity through colchicine soaking to produce polyploid plants. Polyploid plants usually have higher vigor than diploid plants. The purpose of this research was to induce genetic diversity of stevia through colchicine soaking in vitro. Single nodes of sterile stevia clone BS were soaked in colchicine at the concentration of 0.01; 0.02; 0.04; 0.08 and 0.1% for 48 and 72 hours, and in sterile aquadest as a control. Plantlet subcultures were done until MV4 (mutant vegetative 4). Putative mutants were observed by plantlet vigor and stomata analyses on MV5. Vigor of plantlets was observed by counting the number of leaves, nodes, roots, fresh weight and dry weight of the plantlet. Stomata analysis was performed by calculating stomata density, stomata size and chloroplast number in stomata guard cells. Results showed that colchicine soaking treatment increased significantly fresh weight and dry weight of putative mutants. Colchicine soaking treatment increased chloroplast number on stomata guard cell and stomata size, but decreased stomata density. Stevia soaked in colchicine for 48 hours at concentration 0.01-0.04% produce putative mutants with high chromosome numbers. [Key words: poliploidy, stomata, chloroplast, mutant]AbstrakStevia rebaudiana Bert. merupakan tanaman penghasil glikosida steviol yang memiliki tingkat kemanisan 200-300 kali lebih tinggi dibandingkan sukrosa. Glikosida steviol ini diproduksi di daun yang kemudian disalurkan ke bagian tanaman lainnya termasuk batang. Penggunaan klon terbaik stevia merupakan salah satu kunci penting keberhasilan industri gula stevia. Salah satu program pemuliaan tanaman stevia adalah meningkatkan keragaman tanaman melalui mutasi dengan kolkisin sehingga menghasilkan tanaman poliploid. Tanaman poliploid umumnya memiliki vigor lebih baik dibandingkan tanaman diploid. Tujuan dari penelitian ini adalah untuk meningkatkan keragaman stevia melalui peren-daman kolkisin in vitro. Buku tunggal steril stevia klon BS direndam dalam kolkisin dengan konsentrasi 0,01; 0,02; 0,04; 0,08 dan 0,1% selama 48 dan 72 jam dengan perendaman dalam air steril sebagai kontrol. Sub kultur dilakukan hingga MV4 (mutan vegetatif 4). Pengamatan mutan putatif dilakukan meliputi analisis morfologi dan stomata pada MV5. Analisis morfologi dilakukan dengan mengamati jumlah daun, buku, akar, bobot basah serta bobot kering planlet. Analisis stomata dilakukan dengan menghitung kerapatan stomata, ukuran stomata serta jumlah kloroplas pada sel penjaga stomata. Hasil menunjukkan bahwa perendaman stevia pada kolkisin meningkatkan bobot basah serta bobot kering stevia in vitro. Perlakuan perendaman kolkisin meningkatkan jumlah kloroplas pada sel penjaga stomata serta ukuran stomata namun menurunkan kerapatan stomata. Perendaman stevia selama 48 jam pada konsentrasi kolkisin 0,01-0,04% menghasilkan mutan putatif dengan jumlah kromosom tertinggi.[Kata kunci: poliploidi, stomata, kloroplas, mutan]